Intestinal Permeability before and after Ibuprofen in Families of Children with Crohn’s Disease - Samuel A Zamora; Robert J Hilsden; Jon B Meddings; J Decker Butzner; R Brent Scott; Lloyd R Sutherland (Canadian Journal of Gastroenterology)
BACKGROUND: Members of a subset of first-degree relatives of adults with Crohn’s disease have been shown to have an increased baseline intestinal permeability and/or an exaggerated increase in intestinal permeability after the administration of acetylsalicylic acid.